The Effect of Emotional Quotient, and Stress Management on Teacher’s Organizational Commitment in Senior High School in District of Padang Lawas - Siregar, Astri Novia (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This study aimed to determine: (1) the effect of emotional quotient school culture on stress management, (2) the effect of emotional Quotient on teacher’s organizational commitment, (3) the effect of stress management on teacher’s organizational commitment. This study uses quantitative methods, the model used is the path analysis with inferential data analysis techniques. The population in this study are all teachers of senior high school in the district of Padang Lawas, amounting to 214 teachers. The research sample was determined by using a proportional stratified random sampling technique to obtain a sample of 137 teachers. The research instrument used for data collection was a questionnaire. The results of this study found: (1) there is a direct and significant impact of emotional intelligence on work stress management with a correlation coefficient r32 = 0,313 with contribution of the direct effect by 10%, (2) there is a direct and significant influence of emotional intelligence on organizational commitment of teachers with a correlation coefficient R 0,094; (3) there is a direct and significant effect of work stress management on organizational commitment of teachers are direct and significant effect of stress management on organizational commitment of teachers working with a correlation coefficient of 0,217 with a contribution of R = the effect of 5%